1996
DOI: 10.1007/bf00185886
|View full text |Cite
|
Sign up to set email alerts
|

Effects of toluene on microbially-mediated processes involved in the soil nitrogen cycle

Abstract: The effects of toluene on indigenous microbial populations involved in the soil nitrogen cycle were examined. Ammonia oxidation potential (AOP) and nitrite oxidation potential (NOP) were both reduced after incubation with high toluene concentrations for 45 days, with the former activity showing greater sensitivity. KCl-extractable ammonium (NH4+ext) levels increased dramatically in soil exposed to high toluene levels, and arginine ammonification was not significantly affected. Alfalfa-amended soil incubated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…-consuming process contributed to the contrasting results in humid versus semi-arid grasslands. Nitrification is much more sensitive to toluene inhibition than ammonification, and under the experimental conditions of our enzyme assays, nitrification was inhibited (Fuller and Scow 1996). Therefore, the high proteolysis:ammonification ratio in semi-arid grassland and shrubland ecosystems is likely driven by high rates of protease activity relative to amidohydrolase activity, not consumption of NH 4 ?…”
Section: Implications For N Cyclingmentioning
confidence: 86%
“…-consuming process contributed to the contrasting results in humid versus semi-arid grasslands. Nitrification is much more sensitive to toluene inhibition than ammonification, and under the experimental conditions of our enzyme assays, nitrification was inhibited (Fuller and Scow 1996). Therefore, the high proteolysis:ammonification ratio in semi-arid grassland and shrubland ecosystems is likely driven by high rates of protease activity relative to amidohydrolase activity, not consumption of NH 4 ?…”
Section: Implications For N Cyclingmentioning
confidence: 86%
“…[23, [30][31][32], one would expect that soils contaminated with high levels of munitions would have elevated levels of these nitrogenous compounds. However, analysis using data from JAAP group 61 soils also indicated a strong correlation be-tween high TNT and TNB concentrations and NO 3 -N levels.…”
Section: Discussionmentioning
confidence: 99%
“…Selective toxicity to nitrification has been observed with other contaminants as well. Fuller and Scow [19] reported that toluene contamination had no significant effect on ammonification but had a large effect on nitrification. Unlike our findings, they did not observe a recovery of the nitrifying population after a 30-d incubation that followed venting-off the highly volatile contaminant.…”
Section: Discussionmentioning
confidence: 99%
“…As with microbial respiration, ammonification is one process that is carried out by many microorganisms and has been found to be suppressed [18] or unaffected [18–20] following contaminant exposure. Nitrification, however, appears to be consistently sensitive to disturbance [8,11,18–23]. Nitrification is an essential microbially mediated process that is carried out by few groups of microorganisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation